The state of Polish speech pathology and its prospects - Tarkowski, Zbigniew (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
The article analyzes important aspects of speech pathology functioning in Poland. It focuses on many detailed issues related to the identity of the speech pathologist profession, education, specialization and standards of dealing with patients.